Martínez-Torrón, Javier y Rodrigo Lara, Belén (coordinadores), COVID-19 y libertad religiosa, Madrid, Iustel, 2021, 535pp. - Torres Gutiérrez, Alejandro (2021)
Fil: Torres Gutiérrez, Alejandro. Universidad de Valladolid. Facultad de Derecho; España